First year completed and on the way to indexation - Chacón-Diaz, Manuel (2021)
Just one year ago, the APCyCCV quarterly publication began, in search of an adequate space to publicize our scientific experiences in original research, clinical cases and reviews of topics on cardiovascular pathology. After four issues published, we can say that it has been a gratifying experience for the editorial board of the journal, we have been able to appreciate the warm reception of the articles not only by our national readers, but also by the great international scientific community